If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 36 = 4x Reorder the terms: 36 + 2x = 4x Solving 36 + 2x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 36 + 2x + -4x = 4x + -4x Combine like terms: 2x + -4x = -2x 36 + -2x = 4x + -4x Combine like terms: 4x + -4x = 0 36 + -2x = 0 Add '-36' to each side of the equation. 36 + -36 + -2x = 0 + -36 Combine like terms: 36 + -36 = 0 0 + -2x = 0 + -36 -2x = 0 + -36 Combine like terms: 0 + -36 = -36 -2x = -36 Divide each side by '-2'. x = 18 Simplifying x = 18
| 5(d+1)-4d=51-5d | | -6(-6r+3)-6=120 | | 2(6-10m)=10(2m-6) | | x+4+8x=4 | | 8+x=2x | | 23x+43-31+45=3254 | | 6x+9=x-8 | | 5(-6-4n)=-110 | | 4k^2-81=0 | | 2(-10m)=10(2m-6) | | 5r+7R+6R-6= | | 5x^2-33x+40=0 | | 23x+43-31+45=264 | | 2x+6(-4-3x)=72 | | -3(h+1.4)=(5-h)11 | | 5x+5-1.8=14.7 | | 11x+1=x-13 | | 2-n=-(n-2) | | -126=-6(3v+3) | | ((3x)(2x))+4=28 | | x^2+x-12-x^2+x+12=0 | | -6=-2x-4x | | 4(23x+43)=503 | | -2n+14+4n=30 | | -2n+14+4n=3 | | 4x/5=6x-1/3 | | 8n+6=6n-4 | | -12=n-4-5 | | 6r-2(2-r)=6(2r-1) | | 290=4x*y | | 25x+47x=72 | | 2m-m=3 |